2017
DOI: 10.1080/13561820.2016.1262337
|View full text |Cite
|
Sign up to set email alerts
|

International service learning and interprofessional education in Ecuador: Findings from a phenomenology study with students from four professions

Abstract: Combined international service learning (ISL) and interprofessional education (IPE) experiences can move health professional student learning beyond the traditional confines of the classroom and outside uniprofessional ethos. The purpose of this transcendental phenomenological study was to describe the shared experience of health professional students participating in an ISL trip to a small community in Ecuador. The study focused on the learning and collaboration that occurred among students from multiple heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 34 publications
2
73
0
3
Order By: Relevance
“…6 Insights into the educational, systemic, and personal factors contributing to differences among professional cultures can guide innovative educational methodologies towards improvement of interprofessional collaborative practice (IPCP). 8 about the context in which illness develops. 8 about the context in which illness develops.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Insights into the educational, systemic, and personal factors contributing to differences among professional cultures can guide innovative educational methodologies towards improvement of interprofessional collaborative practice (IPCP). 8 about the context in which illness develops. 8 about the context in which illness develops.…”
mentioning
confidence: 99%
“…7 Also, combining service-learning with IPE experiences was found in one study to transform health professions students' learning by taking them outside the confines of the classroom and beyond their specific silos. 8 about the context in which illness develops. They are then encouraged to link oral health and overall health care services to academic coursework as they become global citizen professionals.…”
mentioning
confidence: 99%
“…For this reason, experiential learning involving practical or authentic situations are recommended to encourage students to better understand the individuals they may work with, and allow them to practice, reflect on their experiences and see the effects of their actions, and also receive critical feedback [58]. While there is some research demonstrating the successful application and potential benefits of experiential learning approaches, such as community or international service learning in physiotherapy and other health disciplines, these studies do not explore the impact on patient outcomes and ongoing practice beyond graduation [60][61][62][63]. Therefore, research exploring effective teaching methods that lead to improved patient outcomes is required to ensure students learn to effectively support the health of culturally diverse communities.…”
Section: Discussionmentioning
confidence: 99%
“…Developed to address the shortcomings of previous frameworks, IP-SDM incorporates interprofessionality and the involvement of patient supports [19]. This reflects the fact that decision-making is very context-dependent by considering environmental influences (i.e., social norms, organizational routines, and institutional structures) on decision-making [16].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence varies in both consistency of how SDM is defined [13] and implemented [23–26]. A recent study concluded that implementation of IP-SDM has struggled as the framework, and users of the framework, lack conceptual clarity and minimal implementation guidance [19]. A study conducted by Lloyd and colleagues in 2013 demonstrated the difficulty in SDM implementation, as SDM is a very complex intervention and pre-existing contexts can drastically change implementation success [27].…”
Section: Introductionmentioning
confidence: 99%